2012
DOI: 10.1038/nature10973
|View full text |Cite
|
Sign up to set email alerts
|

An inverse relationship to germline transcription defines centromeric chromatin in C. elegans

Abstract: Centromeres are chromosomal loci that direct segregation of the genome during cell division. The histone H3 variant CENP-A (also known as CenH3) defines centromeres in monocentric organisms, which confine centromere activity to a discrete chromosomal region, and holocentric organisms, which distribute centromere activity along the chromosome length1–3. Because the highly repetitive DNA found at most centromeres is neither necessary nor sufficient for centromere function, stable inheritance of CENP-A nucleosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
193
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(228 citation statements)
references
References 34 publications
27
193
2
Order By: Relevance
“…Thus, CENH3 chromatin is probably far less compatible with regulated transcription. In addition, gene transcription may actively evict CENH3 nucleosomes during periods of development when they cannot be readily replaced (Gassmann et al 2012). Our data strongly support this extensive literature by demonstrating that 12 transcribed genes found in nCenM3 and nCen3 were all located within subdomains depleted of CENH3.…”
Section: Transcription and Neocentromere Establishmentsupporting
confidence: 79%
“…Thus, CENH3 chromatin is probably far less compatible with regulated transcription. In addition, gene transcription may actively evict CENH3 nucleosomes during periods of development when they cannot be readily replaced (Gassmann et al 2012). Our data strongly support this extensive literature by demonstrating that 12 transcribed genes found in nCenM3 and nCen3 were all located within subdomains depleted of CENH3.…”
Section: Transcription and Neocentromere Establishmentsupporting
confidence: 79%
“…These centromeres are discrete point centromeres distributed throughout the chromosomes, each containing a single nucleosome with the centromere-specific histone H3 variant, HCP-3 (a CENP-A homolog, also known as CenH3) (Steiner and Henikoff 2014). Furthermore, C. elegans centromeres tend to associate with regions of low transcriptional activity, possibly due to exclusion of HCP-3 by high histone turnover in regions with active transcription (Gassmann et al 2012;Steiner and Henikoff 2014). Second, the distribution of active genes along C. elegans autosomes is nonrandom, such that the density of active genes is higher in the center than along the arms (Figure 3).…”
Section: Components Of the Nementioning
confidence: 99%
“…In our assay, we also tested the effect of Cnp1 overexpression and consistently found that nearly all cells carrying the centromeric ade6 ϩ marker form red colonies under conditions of Cnp1 overexpression. Correlation between CENP-A occupancy and gene silencing is also reported in Candida albicans neocentromeres, the newly formed functional centromeres at ectopic sites upon loss of the endogenous centromere (52), and in C. elegans, in which CENP-A is distributed broadly throughout the whole chromatin but inversely correlating with transcription of the underlying chromatin regions in germ line (2). Also, reduction or increase in the Cnp1/histone H3 ratio led to reduced or enhanced gene silencing, respectively, in centromere (37).…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, studies in C. elegans embryos showed that in cell divisions, parental CeCENP-A molecules undergo complete turnover after replication. A spatial cue for new CeCENP-A incorporation, instead, is provided by the transcription activity in the germ line (2). Thus, the CENP-A nucleosome inheritance process is unlikely to be conserved in this organism with holocentromeres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation